Atividades preventivas realizadas pelos cirurgiões-dentistas do PSF de Natal-RN - Almeida, Gilmara Celli Maia de (2007)
Family Health Program (FHP) presents itself as a restructured model on basic cares besides having prevention practices and promotion in health as essential parts. According to that, the purpose of this study is to perceive which prevention practices in oral health are accomplished by the dentists from the FHP of Natal-RN as well as the way they have been developed, the knowledge basis to execute the procedure and the use of evaluation instruments by the dentists and by the Oral Health Co-Ordinator. A list of dentists participating on the FHP of Natal in March, 2006 (n= 91) was obtained so it was possible to formulate a structured interview. After excluding those with less than six months attending to the program, and considering the loss, eighty dentists got to be interviewed. It had questions about individual and group preventive procedures, sources of basement to develop the activities and to verify the impact and evaluation instruments. Besides that, an interview was made with the Oral Health Co-Ordinator about the evaluating process and the existence of a protocol as well as about document analysis in the Ambulatory Informations System Unique Health System (AIS-UHS), Information of Basic Care System and Pact of Recorder. The main individual activities consist on Oral Hygiene Orientation (87,5%) and Fluoridization (95%). Group activities remain at scholar groups acts(91,25%) being fluoridization done by 91,25% and educative activities by 86,25% mainly through speeches (61,25%).Orientations about oral cancer were detached on the aged group (39,96%)and hypertensive and diabetic group (19,51%), as well as integration with the health team was respectively 21,93% and 39,02%. Speeches and talk rounds are the main activities for aged, hypertensive and diabetics, and are also expressive to pregnant women. For pregnant women and babies group predominate hygiene and diet orientation. About the evaluation instruments 73,75% of the dentists do not consider their existence, despite 73,75% consider that actions have impact specially due to a increase of hygiene and decrease of caries index on the children. The main sources of basement are clinical experience (42,5%) and preparative courses (33,75%), only 7,5% mentioned population need and local reality. The Oral Health Co-Ordinator related the Attention Pact Recorder and records from the AIS - UHS as evaluation source but also detached the lack of epidemiologic surveying. She mentioned the increase of supervised brushing as a positive result and detached the hardness of the professional to act inside the family and as a team. The AIS-UHS records showed that fluoridization is more used individually and the supervised brushing is predominant as a group action, besides that educative activities at the Health Establishment predominate due to actions at the community. Facing the results, it was verified the act in different groups, special attention given to scholars, as well as focus the activities on caries giving less emphasis to other oral problems. Despite that, there was no epidemiologic instruments or data of the local reality to guide the actions and to be part of the planning and evaluation process